Strategy for Improving the Out Came Quality of Graduates at the Ibnu Rusyd STAI, Kotabumi, North Lampung - Ali, M. Makhrus; Dwistia, Halen; Afifatun, Siti; Hariyati, Tri; Gilani, Syed Iftikhar Ali (Yayasan Azhar Amanaa Yogyakarta, 2023)
This research is a field research, which was conducted at STAI Ibnu usyd Kotabumi. The samples in this study included university administrators, 3 lecturers, 3 students, 3 alumni, industry and stakeholders. In improving the quality of graduates with good outcomes, the strategy undertaken is not only to pay attention to qualified and competent lecturers, but to several aspects, such as content standards, processes, graduate competencies, facilities and infrastructure, management, financing, and educational assessment. Moreover, what must be considered is the implementation of a strategy to improve the quality of graduate outcomes at STAI Ibnu Rusyd Kotabumi which is expected to have a positive impact in producing graduates who are competent and ready to face the demands of the world of work and society.